Differences in the pathogenicity and molecular characteristics of fowl adenovirus serotype 4 epidemic strains in Guangxi Province, southern China - Wei, You; Xie, Zhiqin; Xie, Zhixun; Deng, Xianwen; Li, Xiaofeng; Xie, Liji; Fan, Qing; Zhang, Yanfang; Wang, Sheng; Ren, Hongyu; Wan, Lijun; Luo, Sisi; et al. (Frontiers in Microbiology, 2024)
Starting in 2015, the widespread prevalence of hydropericardium-hepatitis syndrome (HHS) has led to considerable financial losses within China's poultry farming industry. In this study, pathogenicity assessments, whole-genome sequencing, and analyses were conducted on 10 new isolates of the novel genotype FAdV-4 during a HHS outbreak in Guangxi Province, China, from 2019 to 2020. The results indicated that strains GX2019-010 to GX2019-013 and GX2019-015 to GX2019-018 were highly virulent, while strain GX2020-019 exhibited moderate virulence. Strain GX2019-014 was characterized as a wild-type strain with low virulence, displaying no pathogenic effects when 0.5 ml containing 10 6 TCID50 virus was inoculated into the muscle of specific pathogen-free (SPF) chickens at 4 weeks of age, while 10 7 TCID50 and 10 8 TCID50 resulted in mortality rates of 80% and 100%, respectively. The whole genomes of strains GX2019-010 to GX2019-013, GX2019-015 to GX2019-018, and GX2020-019 showed high homology with other Chinese newly emerging highly pathogenic FAdV-4 strains, whereas GX2019-014 was closer to nonmutant strains and shared the same residues with known nonpathogenic strains (B1-7, KR5, and ON1) at positions 219AA and 380AA of the Fiber-2 protein. Our work enriches the research on prevalent strains of FAdV-4 in China, expands the knowledge on the virulence diversity of the novel genotype FAdV-4, and provides valuable reference material for further investigations into the key virulence-associated genetic loci of FAdV-4.